Transgenerational trauma and attachment - Kostova, Zlatomira; Matanova, Vanya L. (Frontiers in Psychology, 2024)
An integrative approach is presented to understand the transmission mechanisms of attachment trauma and the quality of the internal working model through manifestations of bodily symptoms concerning physical and mental health. A case of dissociative symptomatology is described in a woman whose ancestors experienced individual and collective trauma related to the political regime. The approach allows for an analytical view beyond the standard complaints of anxiety, depression, post-traumatic symptoms, eating disorders, etc. A brief description of the transgenerational transmission of trauma is presented.